Critical factors to be considered when planning the implementation of environmental improvements and energy saving - dos Santos, Juliane Barbosa [UNESP]; Jabbour, Charbel José Chiappetta [UNESP] (Academy of Science of South Africa, 2013)
To identify the critical success factors in the adoption of energy efficiency actions in Brazilian hospitals and describe their behaviour are the objectives of this paper. In order to achieve these goals, a literature review was performed on green management and energy efficiency. This was the basis to define the questions of the interview script applied to two hospitals located in the state of São Paulo, Brazil. The interview script application was complemented by secondary data and direct observation. The results showed that: a) the studied hospitals are embracing environmental management actions more often and, whenever possible, energy efficiency actions are taken as well and b) in the cases analysed top management support, commitment with the environment, green process design and employee empowerment were some of the most relevant critical success factors to the accomplishment of energy efficiency actions. These findings may be of interest to emerging countries, including BRICS (Brazil, Russia, India, China and South Africa).
Keywords: Brazil; Critical success factors; Energy efficiency; Green management; Hospitals; Sustainability